The influence of crystalline phase additions on the mechanical properties of dental ceramic materials - Pisitanusorn A. (2014)
The present study is the last part of an evaluation of the reinforcing influence of crystalline phase in dental ceramics subjected to short-time, one-step firing. In this study, four groups of different compositions and types of crystalline Al2O3, TiO2, MgO and ZnO phase mixed with dental ceramic were compared. Twenty bars of each material were prepared according to their compositions and firing conditions. Six composite materials were tested to reveal and compare the relationship between their physical and mechanical properties and microstructures. Flexural strength data were analyzed using a one-way ANOVA with Scheffé post hoc test (p = 0.05) and Weibull statistics. The mean flexural strength (MPa) and fracture toughness (MPa-m1/2) values of all materials were: DA38.6Ti1.4 125.1b, 1.62b; DAf38.6Ti1.4 201.3c, 2.61c; DAf38.6M1.4 125.7b, 1.63b; DAf37.2Zn2.8 135.5b,d, 1.83b,d; DAf34.6Zn5.4 146.3b,d. 2.00d and DAf32.4Zn7.6 152.4d, 2.04d; whereas the dental ceramic was 83.4a, 1.01 a. Values with the same superscript letters showed no statistically significant difference. Microscope investigation and X-ray diffraction revealed that the new phase formed, i.e. nanocomposite structures of spinel and gahnite, plays an important role, based on the relationship between the glassy matrix and the crystalline phase in the strengthening and toughening mechanisms of these composite ceramics. Crystalline phase alumina-metal oxide reinforcement can improve the strength of dental ceramic. Some effects such as porosity, morphology, secondary phase formation and orientation of crystalline phase, are important in determining the mechanical properties of materials.